Maturation, playing position and genetic variation : injury risk factors in high-level youth soccer - Hall, E. (Liverpool John Moores University, 2019)
The negative impact of injury on the development of youth soccer players (YSP) means that efforts must be made to prevent and control their occurrence. Although a range of risk factors have been investigated in YSP, they remain poorly understood due to limitations with previous studies (as discussed in Chapter Two). Greater understanding of the factors affecting injury risk could help identify and improve management of `at risk` players, thus improving the likelihood of them reaching their full potential of a professional contract. Accordingly, the overriding aim of this thesis was to investigate the association of potentially key risk factors with injury risk in a large cohort of high-level YSP from academies within eight professional clubs from four different countries, across two continents. For all four experimental chapters in this thesis, injuries were prospectively recorded over the course of a single season in high-level YSP to determine (i) whether the rate of these injuries varied in YSP between different nations; (ii) if maturation status, playing position and/or genetic variation were associated with injury risk in YSP. The injury audit (Chapter Three) revealed that non-contact injuries to skeletal muscle were amongst those frequently recorded, with most injuries located in the lower limb. The Under-14 (U14) and U16 age groups suffered relatively more severe injuries, with minimal differences in injury rate between nations. Thus, Chapter Three indicated that more severe injuries occurred around the timing of biological maturation, suggesting an association of maturation status with injury in YSP. When this hypothesis was tested directly in Chapter Four, maturation status (pre-, mid- and post- peak height velocity [PHV], estimated by maturity offset) was indeed associated with injury risk, where soft-tissue, ligament/tendon and thigh injuries were more prevalent in post-PHV than pre- and mid-PHV, and muscle injuries were more prevalent in post- than pre-PHV. With all injuries combined, post-PHV missed more days in the season than pre-PHV. Thus, the results from this chapter strongly suggest that post-PHV are at greatest risk of injury, and miss more of the season due to injury than pre- and mid- PHV. Having identified a maturation-dependent link with injury risk in YSP, Chapter Five investigated whether there was an association between playing positon and injuries solely in post-PHV YSP (due to the greater prevalence and severity of injuries in post- vs. pre-PHV, and the fact that playing position is more firmly defined at post-PHV). Prevalence and severity did not differ between outfield positions, but relatively fewer goalkeepers suffered thigh injuries than lateral and forward players combined. These data indicate injury prevention strategies should be similar for outfield players in post-PHV, but should focus on preventing thigh injuries particularly for lateral and forward players. Finally, the results from Chapter Six showed that three single nucleotide polymorphisms (SNPs), i.e. COL5A1 rs12722, EMILIN1 rs2289360 and VEGFA rs2010963, were associated with injury prevalence in pre- and post-PHV combined, and that more SNPs were individually associated with injury risk in post- vs. pre-PHV. When combining those SNPs that were individually associated with injury risk, injured YSP demonstrated a worse polygenic profile (in terms of more `at risk` genotypes) than uninjured YSP regarding non-contact and non-contact soft-tissue injuries, while pre- and post-PHV YSP had similar polygenic profiles. These data indicate a maturation-dependent influence of individual SNPs on injury, i.e. the environment likely interacts with genetic predisposition for injury more so in post-PHV YSP, when the intensity of training/match-play is greater than it is for pre-PHV YSP. The results from this thesis clearly identify post-PHV as being at higher risk of injury than their biologically younger counterparts, and that injury risk is similar between countries in this under-researched and important population. The results also show that playing position in physically mature YSP has minimal influence on injury risk but that genetic variation appears to be linked with the likelihood of suffering certain injuries, as well as the severity of those injuries. These novel findings could be used to help identify and manage `at risk` YSP in order to reduce the burden of injury, thus increasing the chance of talented YSP reaching their full potential of a professional playing career.